FINANCIAL AWARENESS IN EVERYDAY LIFE DUE TO THE PANDEMIC, BASED ON THE RESULTS OF A HUNGARIAN QUESTIONNAIRE SURVEY: Received:13th October 2022; Revised: 20th October 2022, 29th October 2022, 29th October 2022; Accepted: 11th October 2022 - Csiszárik-Kocsir Habil, Agnes; Varga, Janos (PEOPLE: International Journal of Social Sciences, 2022)
The 2008 crisis has taught us a lot in many areas. We have realised the importance of making informed choices in all areas of life, including finance. The importance of financial literacy has been brought into sharp focus as a result of these events, which have highlighted the gaps and knowledge disadvantages that could have prevented the events and disadvantages that most of society suffered as a result of the crisis. However, in many countries, financial awareness is still conceptual, much discussed, researched and studied, but in many cases no real change is visible or tangible. In many cases, awareness programmes and initiatives are still in an experimental phase and are not yet integrated into the day-to-day management of problems. In our study, we aim to demonstrate the practical importance of financial literacy, awareness and culture in everyday life, based on the results of a primary research study conducted in Hungary after the pandemic outbreak, interviewing more than 6800 participants.